A Direct Comparison of Alloderm-Ready to Use (RTU) and DermACELL in Immediate Breast Implant Reconstruction - Zenn, Michael R. (Eplasty, 2016)
The objective of this study was to compare the 2 leading human acellular dermal matrices in breast reconstruction with implants. This retrospective study draws on the experience of 2 expert surgeons with a history of long-standing use of the Alloderm-RTU (LifeCell Corporation, Branchburg, NJ) product who switched to the DermACELL acellular dermal matrix (LifeNet Health, Virginia Beach, Va) product. The consecutive nature of these data over this change allowed comparison between the 2 products without the confounding effects of patient selection or change in technique. The postoperative complications of seroma, infection, implant loss, and unplanned return to the operating room were studied, and no statistical differences were noted between these 2 products. The overall complications rates were low, with implant loss and infection less than 2% in 249 cases. Recommendations are for continued use of acellular dermal matrix in breast reconstruction and product selection based on price and availability.